SISTEM PAKAR IDENTIFIKASI HAMA DAN PENYAKIT CABAI BERBASIS ANDROID (Information Technology and Telematics, 2015)
Abstract-  The chili is one of  the staple foods in everyday  life.  One  factor  is  the  decline  in  the production  of  chilli  pepper  plant  pests  and diseases.  Many  people,  especially  farmers  who confuse pests or diseases that attack the pepper plant  them  so  that  no  one  way  of  handling. Hence  made  an  application  program  that  can identify  (an  activity  that  aims  to  examine  and analyze in more depth will be a thing or object) pests  and  diseases  chili.This  application  program  mimics  the  way  of thinking of a specialist pest and disease chili in identifying  a  disease.  This  application  was created  to  help  in  the  search  for  conclusions about  diseases  that  attack  and  how  to  mitigate them.  This  application  program  development using  inference  reasoning  forward  forward chaining  and  method  of  calculation  with  Bayes theory. The programming language used is Java, and  database  using  SQLite  database  browser. With  this  final  project  can  determine  the identification of plant diseases chili  through the consultation  process  on  the  system  quickly  and efficiently  with  a  mobile  media.Keywords:  Applications,  pepper  plant  disease, Bayes method, Android